Design of HPLC Method for Simultaneous Quantification of Paracetamol and P-Aminophenol in Paracetamol Formulations: Tablets, Syrups and Suspensions - Yahaya, Issah (2016)
A thesis submitted to the Department of Pharmaceutical Chemistry, Kwame Nkrumah University of Science and Technology in partial fulfillment for the degree of Master of Philosophy in Pharmaceutical Chemistry (Pharmaceutical Analysis and Quality Control).